Substrate specificity of an elongation‐specific peptidoglycan endopeptidase and its implications for cell wall architecture and growth of Vibrio cholerae. Issue 5 (29th July 2013) - Dörr, Tobias; Cava, Felipe; Lam, Hubert; Davis, Brigid M.; Waldor, Matthew K.
Summary The bacterial cell wall consists of peptidoglycan (PG), a sturdy mesh of glycan strands cross‐linked by short peptides. This rigid structure constrains cell shape and size, yet is sufficiently dynamic to accommodate insertion of newly synthesized PG, which was long hypothesized, and recently demonstrated, to require cleavage of the covalent peptide cross‐links that couple previously inserted material. Here, we identify several genes in Vibrio cholerae that collectively are required for growth – particularly elongation – of this pathogen. V. cholerae encodes three putative periplasmic proteins, here denoted ShyA, ShyB, and ShyC, that contain both PG binding and M23 family peptidase domains. While none is essential individually, the absence of both ShyA and ShyC results in synthetic lethality, while the absence of ShyA and ShyB causes a significant growth deficiency. ShyA is a D, d‐endopeptidase able to cleave most peptide chain cross‐links in V. cholerae's PG. PG from a ∆shyA mutant has decreased average chain length, suggesting that ShyA may promote removal of short PG strands. Unexpectedly, ShyA has little activity against muropeptides containing pentapeptides, which typically characterize newly synthesized material. ShyA's substrate‐dependent activity may contribute to selection of cleavage sites in PG, whose implications for the process of side‐wall growth are discussed.